2011
DOI: 10.1089/vbz.2010.0088
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Repellent Activities of Some Plant Extracts AgainstSimulium damnosumComplex

Abstract: The root and leaf extracts of four plants, Occimum gratissimum, Azadirachta indica, Pterocarpus santalinoides, and Pistia hyptis, were studied for repellent activities against the adults of Simulium damnosum sensu lato. The leaves and roots were extracted with 95% ethanol and the stocks were diluted with paraffin. The repellent activities of the extracts were investigated using human baits along the banks of River Oyan and River Ogun in southwestern Nigeria. The results showed that the root extract of O. gratt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Previous studies have reported the phytochemical data pertaining to the essential oils present in the leaves of the species growing in Grumari restinga. The studies demonstrated that sesquiterpenes are the main constituents of the leaves of N. obscura , while pinene monoterpenes are the major volatile compounds in the leaves of E. astringens and M. atropurpureum 16 , 33 . Studies on the polar extracts of the leaves demonstrated the presence of phoroglucinols (eugenial C, eugenial D, and eugenial E) and pentacyclic triterpenes (α-amirin, ꞵ-amirin, and betulinic acid) in E. astringens 34 , 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the phytochemical data pertaining to the essential oils present in the leaves of the species growing in Grumari restinga. The studies demonstrated that sesquiterpenes are the main constituents of the leaves of N. obscura , while pinene monoterpenes are the major volatile compounds in the leaves of E. astringens and M. atropurpureum 16 , 33 . Studies on the polar extracts of the leaves demonstrated the presence of phoroglucinols (eugenial C, eugenial D, and eugenial E) and pentacyclic triterpenes (α-amirin, ꞵ-amirin, and betulinic acid) in E. astringens 34 , 35 .…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria, Usip et al ( 2006 ) demonstrated that the volatile oil (essential oil) derived from O. gratissimum could reduce the biting rate of S. damnosum , ranging from 79 to 90 % for at least 3 h after application. The repellent effi cacy of extracts from O. gratissimum against blackfl ies was confi rmed by later study in Nigeria by Sam-Wobo et al ( 2011 ). It was disclosed that the repellents formulated from ethanolic extracts of O. gratissimum roots and Pistia hyptis leaves were effective against S. damnosum with approximately 78 % repellency.…”
Section: Blackfl Iesmentioning
confidence: 90%
“…Previous studies have reported protective effects of cocoa oil (Pitroipa et al , 2002) and coconut oil and palm oil (Sylla et al , 2003) although the exact degrees of protection were not determined. Other studies conducted in Nigeria have demonstrated significant repellent effects of roots and leaf extracts of plants achieving 78 and 78.1% protection with roots of Occimum gratissimum and leaves of Pistia hyptis , respectively (Sam‐Wobo et al , 2011). Another Nigerian study this time using 20% (v/v) volatile oil of O. gratissimum and liquid paraffin applied topically could achieve as high as 90.2% protection against blackfly bites (Usip et al , 2006).…”
Section: Introductionmentioning
confidence: 96%